2019
DOI: 10.1177/0004563219830733
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric reference intervals for plasma anti-Müllerian hormone: comparison of data from the Roche Elecsys assay and the Beckman Coulter Access assay using the same cohort of samples

Abstract: Background Autoanalyser methods for the measurement of anti-Müllerian hormone have been introduced into clinical laboratories but few reports of paediatric reference intervals using these new assays have been published. Methods After prior evaluation of the Roche Elecsys anti-Müllerian hormone assay against the Beckman Coulter modified second generation anti-Müllerian Hormone enzyme-linked immunosorbent assay using samples from adult females, a cohort of paediatric samples which had previously been assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…indicated that AMH concentrations measured with Elecsys AMH were significantly different from that measured with Access AMH assay (Beckman Coulter). 20 Although the median AMH concentrations decrease gradually with age, the range of AMH concentrations at each age group showed significant overlap between age groups throughout 20–50 years old and indicates a significant individual variation of AMH concentrations. This highlights the clinical utility of measurement of serum AMH concentrations which reflect and correlate the antral follicle count and ovarian reserve.…”
Section: Discussionmentioning
confidence: 87%
“…indicated that AMH concentrations measured with Elecsys AMH were significantly different from that measured with Access AMH assay (Beckman Coulter). 20 Although the median AMH concentrations decrease gradually with age, the range of AMH concentrations at each age group showed significant overlap between age groups throughout 20–50 years old and indicates a significant individual variation of AMH concentrations. This highlights the clinical utility of measurement of serum AMH concentrations which reflect and correlate the antral follicle count and ovarian reserve.…”
Section: Discussionmentioning
confidence: 87%
“…After a transient decline postnatally, AMH levels rise in infancy and continue to remain comparatively higher in males until they decline by stages 2 and 3 of puberty as intratesticular testosterone levels start to rise ( 32 ). At this point, AMH levels in postpubertal males are comparable and overlap with AMH levels in females considerably although median AMH remains 2- to 3-fold higher compared with females ( 33 ). Immunohistochemistry has shown that the expression of AMH type 2 receptor parallels AMH in serum declining after puberty in males ( 34 ).…”
Section: Physiological Role Of Amhmentioning
confidence: 79%
“…2 ). Throughout childhood, AMH concentrations are distinctly higher in males (almost 35-fold) ( 51 ), so despite individual variability and a broad normal range, it is easily discriminated from female norms ( 33 ) ( Fig. 2 ).…”
Section: Serum Amh Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] In girls, AMH is extremely low after birth, and then it gradually increases during infancy and childhood. 5 The serum AMH concentrations show strong and positive correlations with the antral follicle count, and it declines steadily with advancing age. 6 AMH is therefore considered an accurate marker in the evaluation of the ovarian follicular reserve.…”
Section: Introductionmentioning
confidence: 95%